The Influence of Policy Implementation of Integrated Activity Monitoring Information System (SIMKET) Apllication Through the Characteristic of Information On Organizational Performance in the Central Bureau of Statistic of South Sumatera - Iman, Guntur Teguh (International Journal of Business, Management and Economics, 2021)
The purpose of this study was to determined the influence of policy implementation of integrated activity monitoring information system (SIMKET) application through the characteristic of information on organizational performance in the central bureau of statistics of South Sumatera. The population was respondents with the criteria of civil servants in the central bureau of statistics of the South Sumatera Province. The sampling method used was proportionate stratified random sampling. The method used in analyzing data is Structural Equation Modeling (SEM). The result of the study found that the implementation of integrated activities monitoring information system (SIMKET) application had an effect on the characteristic of information, characteristic of information had an effect on the organizational performance and the implementation of integrated activities monitoring information system (SIMKET) application had an unsignificant effect on organizational performance.